2012
DOI: 10.1103/physrevlett.108.235701
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Simulation of the Cooperative Jahn-Teller Transition in 1D Ion Crystals

Abstract: The Jahn-Teller effect explains distortions and nondegenerate energy levels in molecular and solid-state physics via a coupling of effective spins to collective bosons. Here we propose and theoretically analyze the quantum simulation of a many-body Jahn-Teller model with linear ion crystals subjected to magnetic field gradients. We show that the system undergoes a quantum magnetic structural phase transition which leads to a reordering of particle positions and the formation of a spin-phonon quasicondensate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 32 publications
(35 reference statements)
0
39
0
Order By: Relevance
“…This effect has received attention for its connections with high-Tc superconductivity and colossal magnetoresistance [18,19,20]. Very recently it was shown that a generalization of interaction (1) can be implemented in a quite natural way in a linear ion crystal placed in a magnetic field gradient [21,22]. The prospects for experimental investigation of the cooperative Jahn-Teller effect would be very interesting, since they would allow us to observe novel quantum structural phase transitions in clean controllable systems.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has received attention for its connections with high-Tc superconductivity and colossal magnetoresistance [18,19,20]. Very recently it was shown that a generalization of interaction (1) can be implemented in a quite natural way in a linear ion crystal placed in a magnetic field gradient [21,22]. The prospects for experimental investigation of the cooperative Jahn-Teller effect would be very interesting, since they would allow us to observe novel quantum structural phase transitions in clean controllable systems.…”
Section: Introductionmentioning
confidence: 99%
“…(25) and keep only the quadratic terms of the density fluctuations. The latter condition can be fulfilled for large coupling g ≫ g c (ρ ≫ 1), where the quantum fluctuations are suppressed [11]. Assuming that the spin and bosonic fields vary smoothly on the scale of lattice constant a in a d dimensional cubic lattice one can perform gradient expansion, such that in the symmetry broken phase g > g c the continuum action becomes…”
Section: B Polar Decompositionmentioning
confidence: 99%
“…The spins are implemented by the internal two metastable levels of the trapped ions where ω z is the effective spin frequency. The desired Jahn-Teller coupling can be realized by the interaction of the spins with an oscillating magnetic field gradient [11,12]. Alternative realization of the Jahn-Teller coupling is based on the interaction of the ions with laser beams propagating in two orthogonal directions tuned near the respective red and blue sidebands [19].…”
Section: Implementation With Quantum Optical Systemsmentioning
confidence: 99%
See 2 more Smart Citations